Preparation of spent coffee grounds-rubber composites using natural rubber latex as binder - MITSAICHON, Varittha; RUAESRIJAN, Kanok-on; PHINYOCHEEP, Pranee; AMORNSAKCHAI, Taweechai; JUNKONG, Preeyanuch; THANAWAN, Sombat (Journal of Metals, Materials and Minerals, 2022)
The aim of this work was to explore the use of natural rubber latex (NRL) as a natural binder (according to the BCG concept) to replace commercial synthetic binders such as polyurethane resin. A composite sheet of spent coffee ground (SCG) and natural rubber (NR) was prepared by mixing of SCG in NRL compounds having concentrations of 30% and 60% dry rubber content (DRC). The amount of SCG in the composites was varied from 33 to 167 part per hundred rubber (phr). The mixture was cast in a mold to form a thin sheet then left drying at room temperature for 24 h. TGA thermogram shows 3 decomposition stages composed of moisture (including volatile matters), polysaccharide and lipid at 44%, 42% and 13% weight, respectively. Hardness (Shore A) increases gradually with increasing the amount of SCG, while tensile strength and elongation at break tend to decrease. Tensile strength decreases from 2.6 MPa to 1.2 MPa for the composites containing 33 phr and 133 phr of SCG, respectively. Alkaline surface treatment of SCG could improve the adhesion between SCG and NR as evidenced by the increase in tensile strength, elongation at break and compression set properties.